Cystic Vestibular Schwannomas Respond Best to Radiosurgery. Issue 3 (September 2017) - Bowden, Greg; Cavaleri, Jonathon; Monaco, Edward; Niranjan, Ajay; Flickinger, John; Lunsford, Dade L.
Abstract : BACKGROUND: : Vestibular schwannomas (VS) have a well‐documented response to Gamma Knife® (Elekta AB, Stockholm, Sweden) Stereotactic radiosurgery (SRS). However, there are limited data available regarding the volumetric response of cystic tumors. OBJECTIVE: : This report correlates the radiographic appearance of VS before radiosurgery with the delayed volumetric response. METHODS: : This study reviewed our SRS experience with 219 VS patients between 2003 and 2013. Patients were treatment naïve and had a significant extracanalicular tumor volume. Magnetic resonance imaging at the time of SRS identified 42 contrast‐enhancing macrocystic tumors, 45 contrast‐enhancing microcystic tumors, and 132 homogeneously enhancing tumors with no intratumoral cyst formation. The median follow‐up was 49.1 months. The median tumor volume was 2.6 cm 3 (0.70–16.1 cm 3 ) and the median dose was 12.5 Gy (11–13 Gy). RESULTS: : The actuarial tumor control rate was 99.4% at 2 years and 96.4% at 5 years. A volumetric reduction of >20% occurred in 85.4% of macrocystic tumors, 76.1% of microcystic tumors, and 62.8% of homogeneously enhancing VS. The median volume decrease per year for macrocystic, microcystic, and homogenous tumors was 17.2%, 7.5%, and 7.9% per year respectively ( P < .001). A 2:1 blinded volumetric case match showed a significant size reduction in macrocystic tumors compared to noncystic tumors ( P = .007). Serviceable hearing was maintained in 61.5% of patients that had Gardner‐Robertson grade I‐II hearing before treatment. Surgical resection or repeat radiosurgery was performed in 8 patients (3.6%) who had sustained tumor progression. CONCLUSION: : SRS provided VS tumor control in >95% of patients, regardless of radiographic characteristics. Tumor volume regression was most evident in patients with cystic tumors.